Critical length parameter of HDPE and its use in fatigue lifetime predictions - Kamila Kozáková; Lukáš Trávníček; Jan Poduška; Jan Klusák (Fracture and Structural Integrity)
The contribution describes the fatigue lifetime predictions of polyethylene notched specimens based on the theory of critical distance. The approach uses the line method, which averages the axial stress over the critical distance. The critical distance is determined from experimental data of Cracked Round Bar (CRB) specimens and specimens with a model notch. From these two sets of experimental fatigue data and corresponding axial stress distributions, the critical distance is determined. The critical distance depends on the number of cycles to failure and notch radius. For this reason, the critical distance is modified by the ratio of stress concentration factors and the modified distance is used for fatigue lifetime predictions of notched specimens with various notch radii. Using this approach significant savings in testing time can be achieved. CRB fatigue tests are commonly used tests for ranking PE pipe grades and are easily available. Adding the fatigue tests of notched specimens with a model notch, the critical parameter can be found, and fatigue lifetime predictions of various notches can be calculated.